Review Of The Murshalah Maslahah Of Credit Card Owners In Cash Withdrawal Transaction - Tektona, Rahmadi (Fundamental: Jurnal Ilmiah Hukum, 2022)
In the development of Islamic economics, especially banking transactions, legal certainty is required regarding whether product transaction activities may be carried out or not, considering that there is no text that can be referred to for this activity. Under these conditions, the process of determining the maslahah mursalah law can be used as an alternative method of determining the law in cash swipe transactions which are a form of deviation from credit cards, in particular the owner of the credit card has the responsibility for using the card if a problem occurs, because the customer has the risk of bad credit due to its misuse, maslahah mursalah is a legal argument for establishing law on new issues. To be able to make mashlahah mursalah as an argument in establishing law, there is a condition that mashlahah is in line with the will of syara' and is included in the type of benefit that is supported by texts in general. Cash swipe activities in Islamic law are included in illegal activities, due to fraudulent engineering of the abuse of credit card functions by purchasing goods that are not in accordance with the original purpose and the existence of usury, and dishonest in its designation, the background is that the author takes the research title review maslahah murshalah on credit card owners in cash swipe activities, with the aim of analyzing and understanding the position of maslahah mursalah on credit card owners in Cash Withdrawal Transaction